Combined detection of preoperative serum CEA, CA19-9 and CA242 improve prognostic prediction of surgically treated colorectal cancer patients - Wang, Jingtao (Int J Clin Exp Pathol, 2015)
We assessed the prognostic significance of preoperative serum carcinoembryonic antigen (CEA), carbohydrate antigen 19-9 (CA19-9) and carbohydrate antigen 242 (CA242) levels in surgically treated colorectal cancer patients. The relationship of preoperative serum CEA, CA19-9 and CA242 levels with disease characteristics was investigated in 310 patients. Correlation between tumor markers was investigated using Pearson correlation test. Univariate and multivariate survival analyses were used to study the relationship between preoperative tumor markers and prognosis [disease free survival (DFS) and overall survival (OS)]. Kaplan-Meier analysis with log rank test was used to assess the impact of tumor marker levels on survival. Positive rate of preoperative serum CEA, CA19-9 and CA242 were 54.84%, 47.42% and 37.10%, respectively. High preoperative CEA level was associated with tumor size (P = 0.038), T stage (P < 0.001) and AJCC stage (P = 0.002). High preoperative CA19-9 level was associated with tumor AJCC stage (P = 0.023). Preoperative CA242 positively correlated with CEA (P < 0.001) and CA19-9 (P < 0.001). Combining the three markers was of independent prognostic value in CRC (HR = 2.532, 95% CI: 1.400-4.579, P = 0.002 for OS; and HR = 2.366, 95% CI: 1.334-4.196, P = 0.003 for DFS). Combined detection of preoperative serum CEA, CA19-9 and CA242 is of independent prognostic value for management of CRC patients treated surgically.